Economic systems analysis and assessment : cost, value, and competition in information and knowledge intensive systems, organizations, and enterprises - Sage, Andrew P.; Rouse, William B. (Hoboken, N.J. : Wiley, 2011)
'This important book fills the need for a textbook on economic systems analysis and assessment, providing extensive coverage on various topics including microeconomic systems and assessment, cost effectiveness, cost estimation for software and systems, strategic investments, and valuation methods. It serves as an effective textbook for senior undergraduate and first-year graduate courses in economic systems analysis and assessment, as well as a valuable reference for engineers and managers involved in information technology intensive systems.'--
'This book provides the fundamentals of economic systems analysis and assessment for engineers and managers concerned with systems engineering and management of systems. No prior background in mathematical programming or economics is assumed, although some exposure to undergraduate micro-economics is recommended. This pertinant discussion of engineering economic systems will be relevant for those who use the subject matter in their professional practice'--
Includes bibliographical references and index.
Keywords: Microeconomics; System analysis